Our country friends - Shteyngart, Gary. (London Allen & Unwin, 2021)
It's March 2020 and a calamity is unfolding. A group of friends and friends-of-friends gathers in a country house to wait out the pandemic. Over the next six months, new friendships and romances will take hold, while old betrayals will emerge, forcing each character to reevaluate whom they love and what matters most. The unlikely cast of characters includes a Russian-born novelist; his Russian-born psychiatrist wife; their precocious child obsessed with K-pop; a struggling Indian American writer; a wildly successful Korean American app developer; a global dandy with three passports; a Southern flamethrower of an essayist; and a movie star, the Actor, whose arrival upsets the equilibrium of this chosen family. Both elegiac and very, very funny, Our Country Friends is the most ambitious book yet by the author of the beloved bestseller Super Sad True Love Story.
Keywords: Quakers; Epidemics